Number 49 (July 2007) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 2007)
(July 2007) - Distribution and Status of Etheostoma tecumsehi, the Shawnee Darter, a Species Endemic to the Pond River, Green River Drainage, Kentucky. By Ronald R. Cicerello and Robert S. Butler Assessment and Control of an Invasive Aquaculture Species: An Update on Nile Tilapia (Oreochromis niloticus) in Coastal Mississippi after Hurricane Katrina. By Pamela J. Schofield, W. Todd Slack, Mark S. Peterson and Denise R. Gregoire Minutes, Business Meeting, 31st and 32nd Annual Meeting, Southeastern Fishes Council Regional Southeastern Fishes Council Reports
Keywords: distribution; status; etheostoma tecumsehi; shawnee darter; pond river; green river; drainage; kentucky; invasive; aquaculture; nile tilapia; oreochromis niloticus; hurricane katrina